Retail food environments, shopping experiences, First Nations and the provincial Norths - Kristin, Burnett (Health Promot Chronic Dis Prev Can, 2017)
INTRODUCTION: This paper looks at the market food environments of First Nations communities located in the provincial Norths by examining the potential retail competition faced by the North West Company (NWC) and by reporting on the grocery shopping experiences of people living in northern Canada. METHODS: We employed two methodological approaches to assess northern retail food environments. First, we mapped food retailers in the North to examine the breadth of retail competition in the provincial Norths, focussing specifically on those communities without year-round road access. Second, we surveyed people living in communities in northern Canada about their retail and shopping experiences. RESULTS: Fifty-four percent of communities in the provincial Norths and Far North without year-round road access did not have a grocery store that competed with the NWC. The provinces with the highest percentage of northern communities without retail competition were Ontario (87%), Saskatchewan (83%) and Manitoba (72%). Respondents to the survey (n = 92) expressed concern about their shopping experiences in three main areas: the cost of food, food quality and freshness, and availability of specific foods. CONCLUSION: There is limited retail competition in the provincial Norths. In Manitoba, Saskatchewan and Ontario, the NWC has no store competition in at least 70% of northern communities. Consumers living in northern Canada find it difficult to afford nutritious foods and would like access to a wider selection of perishable foods in good condition.